2021
DOI: 10.1172/jci.insight.148435
|View full text |Cite
|
Sign up to set email alerts
|

A specific low-density neutrophil population correlates with hypercoagulation and disease severity in hospitalized COVID-19 patients

Abstract: SARS coronavirus 2 (SARS-CoV-2) is a novel viral pathogen that causes a clinical disease called coronavirus disease 2019 (COVID-19). Although most COVID-19 cases are asymptomatic or involve mild upper respiratory tract symptoms, a significant number of patients develop severe or critical disease. Patients with severe COVID-19 commonly present with viral pneumonia that may progress to life-threatening acute respiratory distress syndrome (ARDS). Patients with COVID-19 are also predisposed to venous and arterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
100
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(123 citation statements)
references
References 79 publications
10
100
1
5
Order By: Relevance
“…Though the precise mechanisms are unclear, several functional links have been proposed, including an interaction between the plasminogen, complement, and platelet-activating systems in severe disease ( 2 ). Both neutrophils and LDNs have an increased tendency to spontaneously produce neutrophil extracellular traps (NETs), which has been observed in COVID-19 and suggested to contribute to coagulopathy in COVID-19 ( 92 , 93 ). We identified that both monocytes and LDNs presented transcriptional signatures associated with aggregation as well as homotypic adhesion in severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Though the precise mechanisms are unclear, several functional links have been proposed, including an interaction between the plasminogen, complement, and platelet-activating systems in severe disease ( 2 ). Both neutrophils and LDNs have an increased tendency to spontaneously produce neutrophil extracellular traps (NETs), which has been observed in COVID-19 and suggested to contribute to coagulopathy in COVID-19 ( 92 , 93 ). We identified that both monocytes and LDNs presented transcriptional signatures associated with aggregation as well as homotypic adhesion in severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that LDNs are associated with the suppression of T cell function and proliferation, similar to the findings of the IPA analysis reported in the present study. Thus, the increase in the number of LDNs might be correlated to the severity of infectious diseases, such as sepsis and COVID-19 (38,39,42,43). Additionally, these cells are also known to be endowed with a high propensity to spontaneously produce neutrophil extracellular traps (NETs) (41,54).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, neutrophils do not fractionate along with PBMCs owing to their higher density as compared to mononuclear cells. However, some low-density neutrophils (LDNs) also known as myeloidderived suppressor cells (MDSCs) have been previously shown to get fractionated along with PBMC preparations in certain pathologies, such as coronavirus disease 2019 (COVID-19) (38,39), tuberculosis (40) human Ebola virus disease (41), and also sepsis (42,43). To further support that the source of these genes/ proteins found in module 1 were derived from LDNs, we performed flow cytometry with PBMC samples obtained from the same cohort of septic patients included in the proteomic analysis.…”
Section: Low-density Neutrophilsmentioning
confidence: 99%
“…Between randomization and day 6, virtually all patients demonstrated amelioration of these key laboratory parameters, irrespective of their treatment arm (Table 2). Systemic GM-CSF has been shown to promote the priming of neutrophils in other forms of ARDS, and low density CD24 + activated neutrophils 49 were seen in higher numbers in our COVID-19 cohort, compared with HC. Sargramostim treatment did however not promote this neutrophil activation state (Fig 3b).…”
Section: Effect Of Sargramostim Inhalation On Innate Immune Landscapementioning
confidence: 65%